2′-N-Alkylaminocarbonyl-2′-amino-LNA: Synthesis, duplex stability, nuclease resistance, and in vitro anti-microRNA activity. (15th January 2023) - Takegawa-Araki, Tomo; Yasukawa, Kai; Iwazaki, Norihiko; Utsugi, Masayuki; Furukawa, Hiroyuki; Kumagai, Shinji; Sawamoto, Hiroaki; Obika, Satoshi
Graphical abstract: Abstract: 2′-Amino-LNA has the potential to acquire various functions through chemical modification at the 2′-nitrogen atom. This study focused on 2′- N -alkylaminocarbonyl 2′-amino-LNA, which is a derivative of 2′-amino-LNA. We evaluated its practical usefulness as a chemical modification of anti-miRNA oligonucleotide. The synthesis of phosphoramidites of 2′- N -alkylaminocarbonyl substituted 2′-amino-LNA bearing thymine and 5-methylcytosine proceeded in good yields. Incorporating the 2′- N -alkylaminocarbonyl-2′-amino-LNA monomers into oligonucleotides improved the duplex stability for complementary RNA strands and robust nuclease resistance. Moreover, 2′- N -alkylaminocarbonyl-2′-amino-LNA is a promising scaffold that significantly increases the potency of anti-miRNA oligonucleotides.